Development of direct methods of mathematical physics in works by M. P. Kravchuk - Luchka , T. F.; Luchka , A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Fundamental results in the works of M. P. Kravchuk devoted to the creation and development of the method of moments for differential and integral equations are discussed.